2016
DOI: 10.1007/s13197-016-2202-3
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and rheological properties of starch and flour from different durum wheat varieties and their relationships with noodle quality

Abstract: Starch and flour properties of different Indian durum wheat varieties were evaluated and related to noodlemaking properties. Flours were evaluated for pasting properties, protein characteristics (extractable as well as unextractable monomeric and polymeric proteins) and dough rheology (farinographic properties), while starches were evaluated for granule size, thermal, pasting, and rheological properties. Flour peak and final viscosities related negatively to the proportion of monomeric proteins but positively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
85
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(94 citation statements)
references
References 27 publications
7
85
1
1
Order By: Relevance
“…Similar results for decrease in oil uptake of noodles with greater protein content and protein quality in terms of SDS sedimentation volume has been proposed by other researchers (Wu et al 2006). Kaur et al (2016) reported that a stronger gluten network results in a less permeable outer layer that may serve as an effective barrier against absorption of oil. Although flours with lower protein content exhibits formation of coarser globules on noodle surface during steaming which allows for greater penetration of oil during frying (Moss et al 1987).…”
Section: Cooking Qualitysupporting
confidence: 87%
“…Similar results for decrease in oil uptake of noodles with greater protein content and protein quality in terms of SDS sedimentation volume has been proposed by other researchers (Wu et al 2006). Kaur et al (2016) reported that a stronger gluten network results in a less permeable outer layer that may serve as an effective barrier against absorption of oil. Although flours with lower protein content exhibits formation of coarser globules on noodle surface during steaming which allows for greater penetration of oil during frying (Moss et al 1987).…”
Section: Cooking Qualitysupporting
confidence: 87%
“…It was also reported that swelling proceeded more rapidly after the exudation of amylose and AMLs are prevented from leaching out (Tester & Morrison, 1990). However, the unfractionated starches from both common and durum cultivars/varieties with higher proportion of large granules showed higher SP and vice versa Kaur et al, 2016;Singh et al, 2016). Furthermore, short amylopectin chains with DP 6-12 increased granular swelling, whereas long chains, on the contrary, resulted in the formation of stronger crystalline network leading to reduced swelling (Singh et al, 2010).…”
Section: Swelling Powermentioning
confidence: 96%
“…This was in agreement with the findings of Sakhare et al (2014) who found that DT and ST of bran duster flours (high extraction rate flours) were higher than straight run flours. Kaur et al (2016) reported that dough strength (in particular DT and ST) is not positively related to the protein content of flours, from which it can be inferred that flours with higher protein content may not necessarily have higher dough strength. In a study conducted by Chaudhary et al (2016), it was noticed that the DT and ST increased in wheat varieties as per the quantity of glutenin in their composition.…”
Section: Farinographic Properties Of Wheat Meal and Flourmentioning
confidence: 99%
“…Starch and proteins are the major constituents of wheat flour and they affect the rheological properties of dough and consequently the characteristics of the final baked product (Kaur et al 2016). Siddhartha Kumar et al (2012) defined that glucoamylase (amyloglucosidase) hydrolyzes both 1,4-a-and 1,6-a-glucosidic linkages and releases b-Dglucose from the non-reducing ends of starch and related oligo-and poly-saccharides.…”
Section: Introductionmentioning
confidence: 99%